Sedimentary evolution of lagoons along the Namibian coast reveals fluctuation in Holocene biogeographic faunal provinces, upwelling intensity and sea level - Schüller, Irka; Belz, Lukas; Wilkes, Heinz; Wehrmann, Achim (Frontiers in Earth Science, 2022)
Within the wave-dominated and high-energy depositional environment of the hyper-arid Namibian coast, lagoons and related saltpans represent one of the few regional settings in which sediments originating from both marine and terrestrial sources can accumulate under sheltered conditions. This allows for an approximately continuous depositional record of mid to late Holocene coastal evolution. For this paleoenvironmental reconstruction, 26 sediment cores from six coastal (paleo-)lagoons were taken and investigated along a 430 km-long latitudinal gradient. Based on 56 age determinations of sediments and shell material, the initial formation of the studied lagoons can be dated back to 6.0–5.3 cal kyr BP. The sediment cores present different types of lithoclastic sediments which can be assigned to five sedimentary facies ranging from sand spit sediments rich in shell material to eolian dune sands and evaporites. From these cores, 221 samples of macrobenthic faunal material have been collected and determined to possess 46 shallow marine species. Biogeographic analyses have resulted in the identification of 10 (sub-)tropical warm water species that are not part of the regional benthic fauna in the present upwelling system. Age determinations of the shell material revealed four phases of biogeographic range expansion/shift into the study area, at 5.3 cal kyr BP, 2.8 cal kyr BP, 1.2–0.9 cal kyr BP, and 0.36–0.12 cal kyr BP from both the northern tropical Angola Current as well as from the southern subtropical Agulhas Current. The combination of datasets from this study with published datasets of regional sea-level fluctuations and upwelling intensities presents an apparent correlation between both processes and presumably an additional linkage to the ENSO and Benguela Niño variability.